O mito tradicional do herói e a integração de luzes e sombras no herói compreensivo - Gonçalves Teixeira, Rafael; Correa, Angela Miguel (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
The hero’s journey as proposed by Joseph Campbell and the anti-hero figure as described by Christoph Vogler are revisited and revised in this essay, where we add to them Agnes Heller’s notion of everyday life, thus resulting in a new kind of hero which we qualify as comprehensive. Differing from anti-heroes, comprehensive heroes do not only establish a dialogue with their dark sides, but also dive in a genuine everyday experience, thus amplifying their humanity and empathy from the public. Such notion has its affinities with the notions of uncertainty (Edgar Morin), complementarity of opposites (Carolina Klautau) and imaginary (Gilbert Durand). The integration of light, shadow and everyday life helps to propose a new idea of a contemporary hero.